Identification and Mitigation of Soil Erosion in Tropical Regions using Nuclear Techniques - Kimpinde, Jules Lwembe; Muteba, Yvan; Kumar, Sangith (Journal of Physical Sciences, 2025)
Purpose: The process of soil erosion involves the separation, movement and deposition of soil particles as a result of a variety of circumstances, including wind, rain, and human activity. It poses important threats to agricultural productivity, water quality and ecosystem stability, necessitating effective management strategies or sustainable land use and conservation efforts. The purpose of this research is to utilize nuclear techniques for soil erosion identification and mitigation in tropical regions. This study investigate the efficacy of nuclear method to diagnose erosion dynamics, quantify rates and inform sustainable land management strategies for mitigating soil erosion in tropical regions. Methodology: Nuclear tracing methods, such as Cesium 137, X-ray fluorescence (XRF), lead-210, Chlorine-36, and Beryllium-7 are capable of providing an incredible amount of data on soil loss rates correlated to drill and sheet erosion, as well as the movements and redistribution of that sediment across the tropical regions. This research conducted a comparative assessment of nuclear tracing methods to evaluate their effectiveness in quantifying erosion rates and understanding soil redistribution processes. Findings: Finding converged across methods, offering valuable insights into erosion quantification, spatial characterization and the impact of farming practices. Nuclear techniques have been created in response to the shortcomings of traditional strategies, offering erosion evaluation at a lower cost and with greater speed. Unique Contribution to Theory, Practice and Policy: These results underline the efficacy of nuclear techniques as vital supplements and alternatives to traditional methods in addressing soil erosion hazards.